Sustainable soil improvement and water use in agriculture: CCU enabling technologies afford an innovative approach. (July 2019) - Lake, J.A.; Kisielewski, P.; Hammond, P.; Marques, F.
Highlights: The ability of a novel CCU fertiliser product was tested for improvements in soil physical and chemical attributes. Soil water retention was significantly enhanced. Soil pH significantly increased. Soil microbial colonisation and crop biomass significantly increased. Otherwise lost-to-atmosphere carbon contributes to the mechanism-of-action for soil improvement. Abstract: With industrial CO2 -emission reduction the heart of carbon capture enabling technologies, we report on a solution engineered to potentially redress the issues of soil improvement and sustainable use of fresh water for food production. In a laboratory-scale pilot study, we demonstrate the capabilities of an innovative and novel product utilising carbon-capture to restore soil properties critical for crop production. In the first study of its kind, the carbon-initiated mode-of-action resulted in changes to soil physical and chemical properties. Soil water retention in a range of soil types was significantly increased by up to 62%; soil pH increased by 0.7–1.1 units: soil microbial colonisation increased by ˜20% over the short term and crop biomass was enhanced by up to 38%. These results give impetus for developing CCU technologies to address environmental issues.